PERCEPTIONS OF STUDENTS WITH VISUAL IMPAIRMENT ON INCLUSIVE EDUCATION: A NARRATIVE META-ANALYSIS - Hisae Miyauchi; Peter V. Paul (Human Research in Rehabilitation, 2020)
This study focused on the perceptions of students with visual impairment. A narrative meta-analysis was utilized to synthesize the findings of investigations that employed quantitative, qualitative, or mixed methodological designs. Based on the contents of the reviewed articles, three broad categories were established: barriers, feelings of acceptance, and successful components of inclusion. Barriers included the physical environments of schools, accessibility, and social interactions. With respect to feelings of acceptance, the constructs of homophily and fitting in were discussed. Several components of successful inclusion were delineated such as a positive school climate and a positive, supportive attitude associated with teachers, especially those who possess knowledge and skills and held high expectations for students. Students with visual impairment also needed skills to be autonomous and assertive, which are conducive to academic success and the initiation and building of friendships with sighted peers. A number of findings of the present study corroborated those from previous investigations; however, the uniqueness of this seminal research pertains to the specific perceptions of students with visual impairment in inclusive settings. Limitations of the study were also discussed.